Febrile-range hyperthermia accelerates caspase-dependent apoptosis in human neutrophils - Nagarsekar, Ashish (2008)
Human neutrophilic polymorphonuclear leukocytes (PMNs) are central to innate immunity and are responsible for clearance of pathogens. PMNs undergo a tightly regulated apoptosis program that allows for timely clearance of PMNs without extravasation of toxic intracellular contents. We investigated the rate of spontaneous apoptosis of human peripheral blood PMNs cultured at basal (37°C) and febrile-range (39.5°C) temperatures (FRT). We found that PMN apoptosis is accelerated at FRT, reaching ~90% completion by 8 h at 39.5°C vs. 18 h at 37°C based on morphologic criteria. Caspase-8 activation peaked within 15 minutes of PMN exposure to FRT and subsequent activation of caspase-3 and -9, cleavage of the BH3 only protein Bid, and mitochondrial release of cytochrome c were also greater in FRT-exposed PMNs. Inhibition of caspase-3, -8, and -9 conferred comparable protection from apoptosis in FRT-exposed PMNs. These results demonstrate that exposure to FRT enhances caspase-8 activation and subsequent mitochondrial-dependent and mitochondrial–independent apoptosis pathways. The PMN survival factors G-CSF, GM-CSF, and IL-8, each prolonged PMN survival at 37°C and 39.5°C, but did reduce the difference in survival at the two temperatures. In a mouse model of intratracheal endotoxin-induced alveolitis, co-exposure to FRT (core temperature ~39.5°C) doubled the proportion of bronchoalveolar PMNs undergoing apoptosis compared with euthermic mice. This process may play an important role in limiting inflammation and tissue injury during febrile illnesses.